Effector and Memory T cell Responses to Commensal Bacteria - Belkaid, Yasmine (2013)
Barrier surfaces are home to a vast population of commensal organisms that together encode millions of proteins, each of them possessing several potential foreign antigens. Regulation of immune responses to this enormous antigenic load represents a tremendous challenge for the immune system. Tissues exposed to commensals have developed elaborate systems of regulation including specialized populations of resident lymphocytes that maintain barrier function and limit potential responses to commensal antigens. However, in settings of infection and inflammation these regulatory mechanisms are compromised and specific effector responses against commensal bacteria can develop. This review discusses the circumstances controlling the fate of commensal specific T cells and how dysregulation of these responses could lead to severe pathological outcomes.